2010
DOI: 10.1080/08832320903449568
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a Program Designed to Demonstrate Continuous Improvement in Teaching at an AACSB-Accredited College of Business at a Regional University: A Case Study

Abstract: This article provides a detailed statistical analysis of a process intended to demonstrate continuous improvement in teaching at an AACSB accredited college of business. The Educational Testing Service's SIR II student evaluation instrument was used to measure teaching effectiveness. A six-year longitudinal analysis of the SIR II results does not indicate improvement in the overall teaching. The results indicate two important concerns when designing a procedure to demonstrate teaching effectiveness. First, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Martell (2007) surveyed deans of accredited business schools (n = 154) about AOL practices and summarized that while "many schools have made great strides in developing systems to collect assessment data," the whole purpose is to "use this data to improve the curriculum" and enhance decision making (2007, p. 192); however, the effects are not yet evident. Pritchard, Saccucci, and Potter (2010) took this assessment one step further to determine whether AOL had affected instructional effectiveness at an AACSB accredited American college of business. Pritchard, Saccucci, and Potter (2010) took this assessment one step further to determine whether AOL had affected instructional effectiveness at an AACSB accredited American college of business.…”
Section: Limited or No Effect?mentioning
confidence: 99%
See 1 more Smart Citation
“…Martell (2007) surveyed deans of accredited business schools (n = 154) about AOL practices and summarized that while "many schools have made great strides in developing systems to collect assessment data," the whole purpose is to "use this data to improve the curriculum" and enhance decision making (2007, p. 192); however, the effects are not yet evident. Pritchard, Saccucci, and Potter (2010) took this assessment one step further to determine whether AOL had affected instructional effectiveness at an AACSB accredited American college of business. Pritchard, Saccucci, and Potter (2010) took this assessment one step further to determine whether AOL had affected instructional effectiveness at an AACSB accredited American college of business.…”
Section: Limited or No Effect?mentioning
confidence: 99%
“…More recently, Kelley, Tong, and Choi (2010) reported that minor alterations to existing courses and improved coordination of multisection courses were the most frequent changes to improve student learning due to AOL. Pritchard, Saccucci, and Potter (2010) took this assessment one step further to determine whether AOL had affected instructional effectiveness at an AACSB accredited American college of business. Over a six year period, these authors reported no change (as assessed by the Educational Testing Service Student Instructional Report [SIR II], a measure of student perceptions).…”
Section: Limited or No Effect?mentioning
confidence: 99%
“…While there has been little research performed on business mathematics specifically, those studies that have analyzed business mathematics have not indicated differences in teaching practices from those of other mathematics professors (Pritchard, Saccucci, & Potter, 2010;Truell & Woolsey, 2008).…”
Section: Professor Perceptions Of Teachingmentioning
confidence: 99%
“…In business mathematics, professors and administrators sometimes struggle to effectively measure the quality of the curriculum and instruction (Pritchard et al, 2010).…”
Section: Current Practices In Curriculummentioning
confidence: 99%
“…Previous work that leverages a CI approach to assessment in the online space showed positive results in improving course design and student outcomes, as well as providing a roadmap for future course improvements (Aggarwal & Lynn, ). The approach has also been used to demonstrate CI in teaching by using student evaluations as measurement items (Pritchard, Saccucci, & Potter, ).…”
Section: Introductionmentioning
confidence: 99%